Efficacy of commercially available biological agents for the topical treatment of cervical intraepithelial neoplasia: a systematic review - Mutombo, Alex Baleka (Syst Rev, 2019)
BACKGROUND: Cervical cancer is a major public health issue in the world, especially in developing countries. It can be prevented through vaccination against HPV (primary prevention) and through screening and treatment of cervical intraepithelial neoplasia (CIN) (secondary prevention). Surgical methods for treatment of CIN are linked to complications such as bleeding and adverse pregnancy outcomes. Furthermore, these methods are not generally available in resource-poor settings. Therefore, topical agents for local application on the cervix have been used since decades to overpass complications and limitations of the surgical methods. AIMS: Review of the literature on the efficacy of commercially available biological agents used for topical treatment of cervical intraepithelial neoplasia (CIN). METHODS: A systematic search through PubMed and the Cochrane database was performed up to December 2017, using the medical subheadings (MesH) for topical agent, treatment, and cervical intraepithelial neoplasia. Appropriate inclusion/exclusion criteria have been used for the selection of eligible clinical studies. Clinical studies containing a minimum of 20 women, aged 18–50 with a diagnosis of CIN 1–3, and at least a 4 weeks follow-up after the end of the topical treatment were included. RESULTS: The initial electronic database search resulted in a total of 849 articles. After screening titles and abstracts, 62 articles were selected as potential studies. Of these, six articles were included in the review after reading the full text: two were on 5-FluoroUracil, two on trans retinoic acid, one on Imiquimod, and one on Cidofovir. The reported regression/remission rates for CIN differed among studies. In CIN2 patients, the overall remission rate ranged between 43 and 93% for the active agents. CONCLUSION: Among the topical agents studied, 5-FluoroUracil showed good remission rates above 80%. Varying results seen in this review is due to the differences in quality of the design between studies. Large-scale and less biaised studies are needed to elucidate the true efficacy and safety of topical agents in the treatment of CIN. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13643-019-1050-4) contains supplementary material, which is available to authorized users.